2020
DOI: 10.1089/ten.teb.2019.0283
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Inducible Factor-1α in Osteochondral Tissue Engineering

Abstract: Damage to osteochondral (OC) tissues can lead to pain, loss of motility, and progress to osteoarthritis. Tissue engineering approaches offer the possibility of replacing damaged tissues and restoring joint function; however, replicating the spatial and functional heterogeneity of native OC tissue remains a pressing challenge. Chondrocytes in healthy cartilage exist in relatively low-oxygen conditions, while osteoblasts in the underlying bone experience higher oxygen pressures. Such oxygen gradients also exist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 112 publications
(123 reference statements)
0
24
0
1
Order By: Relevance
“… 157 Growth factors and cytokines also participate in OA pain via both cartilage degradation and nociceptive stimulation. Pain relief has been observed for therapies targeting inflammatory mediators such as TNF, 158 IL-1 β, 159 IL-6 160 and PG-E2, 161 signaling mediators such as p38, 162 HIF 163 and RUNX2, 164 and proteinases such as MMP 165 and ADAMTS-5. 166 …”
Section: Subchondral Bone Microenvironment and Oa Painmentioning
confidence: 99%
“… 157 Growth factors and cytokines also participate in OA pain via both cartilage degradation and nociceptive stimulation. Pain relief has been observed for therapies targeting inflammatory mediators such as TNF, 158 IL-1 β, 159 IL-6 160 and PG-E2, 161 signaling mediators such as p38, 162 HIF 163 and RUNX2, 164 and proteinases such as MMP 165 and ADAMTS-5. 166 …”
Section: Subchondral Bone Microenvironment and Oa Painmentioning
confidence: 99%
“…HIF-1α serves as a key factor for maintenance of hyaline chondrocyte phenotype by promoting the synthesis of type II collagen and aggrecan [ [47] , [48] , [49] , [50] , [51] ]. Depletion of HIF-1α can induce chondrocyte apoptosis and aggravate cartilage degeneration in OA [ [52] , [53] , [54] ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the positive impact of bioreactors in musculoskeletal tissue engineering has been well-established (Peroglio et al, 2018) and electrospun scaffolds coupled with bioreactors have shown promise todate, even for complex structures, such as the cartilage-bone interface (Baumgartner et al, 2019). Further, considering that extracellular matrix is key modulator of cell fate through provision of biophysical, biochemical, and biological signals Watt and Huck, 2013;Kumar et al, 2017;Muncie and Weaver, 2018;Smith et al, 2018;Novoseletskaya et al, 2019), strategies that enhance and accelerate native extracellular matrix synthesis [e.g., hypoxia (Taheem et al, 2019)] and deposition [e.g., macromolecular crowding ] coupled with electrospinning are likely to lead to more biomimetic three-dimensional cartilage equivalents. It is also worth noting, that although the cell-sheet/scaffold-free technology has shown promise in human cartilage engineering (Sato et al, 2019), only thin layers of tissue can be developed, which imposes the need of either multi-layered approaches that are often associated with delamination and cell death in the middle layers due to poor nutrient/waste transport (Sekine et al, 2011) or multiple surgeries (Shimizu et al, 2006;Komae et al, 2017).…”
Section: Critical Analysis and Outlookmentioning
confidence: 99%